Improving the performance of student teams in project-based learning with Scrum - Dinis-Carvalho, José (2021)
The purpose of this paper is to analyze the effectiveness of Scrum for project and team management in PBL teams in higher education. To attain this goal, a study was carried out to analyze students’ perceptions about Scrum as an effective method for PBL teams. Based on two different editions of PBL that used the Scrum method with different characteristics in each approach, this paper aims to identify the best practices for effective team and project management and draw recommendations for successful use of scrum in PBL approaches. The authors used an exploratory case study carried out within an engineering program at the University of Minho, Portugal. The research design was based on an explorative quantitative and qualitative approach. Implementing Scrum in PBL teams helps students to keep the project running smoothly and draws greater awareness on how to manage the project and teams in a more effective way. Findings show that task assignment, performance monitoring, visual management and regular feedback were considered the main advantages of using Scrum in PBL teams, which had a positive impact on student performance. However, for the success of Scrum, students recognize the role of the Scrum Master and Project Owner as vital to guide the teams in a sustainable way. Research on the application of Scrum in Education is scarce and mostly exploratory. This paper is among the very few empirical studies consolidating knowledge on the implementation of Scrum approaches to improve learning in higher education. More specifically, it brings a valuable contribution on how to improve specifically team performance in PBL teams with the use of agile approaches such as Scrum.